Estimating and Analyzing Food Security Indicators in Selected Arab Countries for the Period (1996 - 2012) - النجفي, عماد حسن; غازي, ليث لؤي (Journal of Economics and Administrative Sciences, 2018)
The study hypothesize that the majority of Arab countries  show a poor agricultural economic efficiency which resulted in a weak productive capacity of wheat in the face of the demand, which in turn led to the fluctuation of the rate of self-sufficiency and thus increase the size of the food gap. The study aims at estimating and analyzing the food security indicators for their importance in shaping the Arabic agricultural policy, which aims to achieve food security through domestic production and reduce the import of food to less possible extent. Some of the most important results reached by the study were that the increase in the amount of consumption of wheat in the countries of the sample did not come only from the increase in production but also from large quantity of imported wheat during the study period. The study also found a significant food gap in the Arab countries, including Iraq, in most of the major food commodities including wheat, a fact that is a result of deficit in the agricultural sector to meet the local needs of these goods. A number of recommendations were suggested in the study  including i.e  following successful agricultural policies that encourage investors and agricultural producers in the Arab countries, whether they are active in the private sector or mixed private and public sectors .This can be accomplished by providing inputs to agricultural production inputs including fertilizers, pesticides and seeds in addition to  modern technology at affordable prices, while  expanding the  areas cultivated with  wheat crops  in order to counter the domestic inability of production of the crop in question in quantities sufficient to meet the growing domestic demand  for a crop that is a  major commodity  both locally and the Arab country level. The study also recommends the support, development and implementation of the results of agricultural research in the Arab homeland countries and encourages common agricultural research between the Arab countries